2020
DOI: 10.1002/art.41299
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Serum Interleukin‐6 Levels With Severe Progression of Rheumatoid Arthritis and Increased Treatment Response Differentiating Sarilumab From Adalimumab or Methotrexate in a Post Hoc Analysis

Abstract: Objective The development of biomarkers to guide treatment decisions is a major research focus in rheumatoid arthritis (RA). Patients with RA have elevated interleukin‐6 (IL‐6) levels; however, the utility of IL‐6 as a predictor of treatment response is unclear. This study was undertaken to investigate, by post hoc analysis, whether baseline IL‐6 levels are predictive of sarilumab treatment responses in 2 phase III studies. Methods Serum IL‐6 concentrations were measured in patients with RA prior to receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
1
24
0
2
Order By: Relevance
“…The beneficial effects of sarilumab versus adalimumab on HRQoL were greater in patients with high IL-6 levels at baseline indicating that among adult RA patients with moderate-to-severely active RA who have had an inadequate response or intolerance to one or more DMARDs, high IL-6 levels may predict greater improvements in PROs/HRQoL than low IL-6 levels. These findings support previous analyses which have shown that across various endpoints, patients with elevated baseline IL-6 levels compared with those without responded better to sarilumab compared with methotrexate or adalimumab [36].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The beneficial effects of sarilumab versus adalimumab on HRQoL were greater in patients with high IL-6 levels at baseline indicating that among adult RA patients with moderate-to-severely active RA who have had an inadequate response or intolerance to one or more DMARDs, high IL-6 levels may predict greater improvements in PROs/HRQoL than low IL-6 levels. These findings support previous analyses which have shown that across various endpoints, patients with elevated baseline IL-6 levels compared with those without responded better to sarilumab compared with methotrexate or adalimumab [36].…”
Section: Resultssupporting
confidence: 90%
“…A separate post hoc analysis of clinical endpoints evaluated in the MONARCH RCT [36] demonstrated that patients with high serum IL-6 levels prior to treatment with sarilumab or adalimumab had increased baseline disease activity, joint damage, pain, and lower patient global assessment and HRQoL scores, and less likely to benefit from TNFi therapies. Furthermore, patients with high versus normal IL-6 levels reported lower responses to placebo plus methotrexate or adalimumab compared with sarilumab treatment [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the median baseline CRP was signi cantly higher in the IL-6i as compared to the TNFi (1.74 mg/dL versus 1.02 mg/dL; p = 0.02). Several studies have found RA patients with high IL-6 levels had a greater response to IL-6i compared to TNFi [27][28][29][30]. Most recently, a post hoc analysis by Boyapati et al evaluated whether baseline IL-6 levels are predictive of sarilumab treatment responses in 2 phase III studies [29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, circulating IL-6 and IL-17 in RA patients have been shown to correlate with depression symptoms, which is a condition also known to be associated with reduced HRV [ 51 , 109 , 110 ]. Furthermore, the use of an IL-6 inhibitor in RA seems to have a more significant clinical effect on patients with higher levels of circulating IL-6 [ 111 ].…”
Section: Cap and Autoimmune Diseasementioning
confidence: 99%